The Influence of Electronic Word of Mouth and Price on Purchase Interest in Hotels in Bali - Kennedy, Roykent; Suastini, Ni Made; Adyatma, Prastha (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study was conducted with the aim of investigating the influence of Electronic Word of Mouth (E-WOM) and price on purchase intention in hotels in Bali. The population in this study were consumers who had never stayed at a hotel in Bali, but had seen online reviews on Google My Business of hotels in Bali. A total of 100 respondents were sampled in this study. The data analysis techniques applied were Multiple Linear Regression, Partial Test, Simultaneous Test, and Determination Coefficient Test. The results of the study demonstrated a positive and significant influence, both partially and simultaneously, of E-WOM and price on purchase intention with an influence of 38.7%. The suggestion that can be given is that the management is expected to increase the effectiveness of the marketing strategy used and evaluate other promotional strategy options to be able to further increase the purchase intention of hotel consumers in Bali.